Profil Penyakit Kulit Penduduk Perkampungan Terapung Kepulauan Tihi-tihi dan Selangan, Bontang, Kalimantan Timur, Indonesia - Fenny Leets Santoso; Anis Irawan Anwar; Farida Tabri; Safruddin Amin; Anni Adriani; Idrianti Idrus; Andi Anwar Arsyad (Cermin Dunia Kedokteran, 2024)
Introduction: Tihi-tihi and Selangan Islands, floating village areas in Bontang, East Kalimantan, are remote areas in Indonesia, which can only be accessed by sea route. The research was conducted to describe skin diseases in those islands. Method: Retrospective observational cross-sectional and descriptive analysis study on floating communities in Tihi-tihi and Selangan Island, Bontang Lestari Village, South Bontang District, Bontang City, East Kalimantan, Indonesia. Results: The study was conducted on 95 subjects, mostly female (53%), and the largest age group was 26-45 years (29%), followed by the 5-11 years group (24%). Skin infection diseases (58.96%) were dominated by scabies (67.9% of the skin infection disease group). The second highest was allergic contact dermatitis (41%) from the non-infection group. There is an association between age and disease group (p<0.05), with an odds ratio of 3.164. Conclusion: Skin diseases in Tihi-tihi and Selangan Islands are dominated by scabies, followed by allergic contact dermatitis. The pediatric age group is at a three-fold greater risk of developing skin infections than non-infection skin diseases.